High-Power Hybrid Mode-Locked External Cavity Semiconductor Laser Using Tapered Amplifier with Large Tunability - Schmitt-Sody, Andreas; Velten, Andreas; Liu, Ye; Arissian, Ladan; Diels, Jean-Claude (Research Letters in Optics, 2008)
We report on hybrid mode-locked laser operation of a tapered semiconductor amplifier in anexternal ring cavity, generating pulses as short as 0.5 ps at 88.1 MHz with an average power of 60 mW. The mode locking is achieved through a combination of a multiple quantum well saturable absorber (>10% modulation depth) and an RF current modulation. This designedlaser has 20 nm tuning bandwidth in continuous wave and 10 nm tuning bandwidth in modelocking around 786 nm center wavelength at constant temperature.